2009
DOI: 10.1016/j.bpj.2009.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Parameters on the Main Phase Transition of Supported Lipid Bilayers

Abstract: Supported lipid bilayers composed of 1-palmitoyl-2-oleoyl-phosphatidylethanolamine (POPE) and 1-palmitoyl-2-oleoyl-phosphatidylglycerol (POPG) were assembled by the vesicle fusion technique on mica and studied by temperature-controlled atomic force microscopy. The role of different physical parameters on the main phase transition was elucidated. Both mixed (POPE/POPG 3:1) and pure POPE bilayers were studied. By increasing the ionic strength of the solution and the incubation temperature, a shift from a decoupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
146
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(167 citation statements)
references
References 53 publications
11
146
1
1
Order By: Relevance
“…In the latter case a strong coupling between the two leaflets could be the reason for the same lateral mobility. We recently demonstrated that the interleaflet coupling is strongly related to the experimental details of the sample preparation, including preparation temperature and the type of support (Seeger et al, 2009b;Seeger et al, 2010). So, it is not always possible to compare the obtained results even if related to the same system.…”
Section: Chapter 1: Supported Lipid Bilayers With Reconstituted Membrmentioning
confidence: 96%
See 1 more Smart Citation
“…In the latter case a strong coupling between the two leaflets could be the reason for the same lateral mobility. We recently demonstrated that the interleaflet coupling is strongly related to the experimental details of the sample preparation, including preparation temperature and the type of support (Seeger et al, 2009b;Seeger et al, 2010). So, it is not always possible to compare the obtained results even if related to the same system.…”
Section: Chapter 1: Supported Lipid Bilayers With Reconstituted Membrmentioning
confidence: 96%
“…In terms of membrane protein/lipid interactions, the distribution of either GPI-anchored proteins, lipidated proteins or transmembrane proteins in the presence of phase separation in lipid bilayers is particularly relevant for understanding trafficking processes of the membrane and the possible influence of phase separation on transmembrane protein function. This topic has been studied by AFM (Milhiet et al, 2002;Seeger et al, 2009b). In the following, we will concentrate on studies performed on these types of membrane proteins.…”
Section: Chapter 2: Lipid/protein Interaction Studied By Afmmentioning
confidence: 99%
“…(1) melting of domains (i) to (ii), i.e., (ii): 0→100%; (2) melting of domains (ii) to (iii), i.e., (iii): 0→100%, by the van't Hoff equation. 34,39,41 Assuming that the standard melting enthalpy ( H) is independent of the temperature, …”
Section: Feng Et Al Previously Reported Similar Afm Images Of the Sumentioning
confidence: 99%
“…Th e answer to this question requires a detailed study of the chemical-physical properties of Supported Lipid Bilayers. In this analysis we will compare the chemical-physical properties as measured with AFM on SLBs with those of other model systems [37]. We will also make use of data obtained by other techniques, especially fl uorescence techniques, on SLBs.…”
Section: Chemical-physical Properties Of Supported Lipid Bilayersmentioning
confidence: 99%
“…In light of the previous discussion on the infl uence of the support on the lipid bilayer it is straightforward to attribute the particular observed behavior to the eff ect of the solid support on the properties of the assembled planar bilayer. Figure 7.4 shows the evolution of the two phase transitions in two plots which allow to derive the van't Hoff enthalpy for each transition [37]. On the basis of this analysis and by comparing the AFM results with the thermodynamic enthalpy obtained from Diff erential Scanning Calorimetry (DSC) on liposomes of the same lipid composition it is possible to extract the average size, in terms of numbers of molecules, of the cooperative unit, which represents the number of lipids in an intrinsic domain [80].…”
Section: Transitions Induced By Temperaturementioning
confidence: 99%